COMPARISON OF THE SIGNIFICANCE OF SOME FIXED FACTORS ON MULTI LEVEL CHILD SURVIVAL - Luguterah, Albert; Nokoe, Kaku Sagary (European Scientific Journal, ESJ, 2013)
A major outcome of the Millennium Development Goals is to reduce child mortality. However, efforts in dealing with this challenge do not seem to lead to desirable levels of satisfaction. In developing Countries, especially in sub Saharan Africa, availability of adequate and reliable statistics that will guide the application of scarce resources and effort can be cited as plausible reasons for this. In this study, Non Parametric methods were used in a Multi level study of Child survival to estimate the survival and hazard functions as well as test for differences in survival functions and regress some prognostic factors at the various levels of child growth. The study showed that in Ghana, 1 out of every 10 children born would not survive by year five, 60.70% of them in the first year with 32.84% of them in the first month. Approximately 29.53% of those who lose their lives in the first five years do so in the first 8 days of life. Among the factors tested, whether a child was a singleton or not was shown to most significantly affect child survival. As a child grows, some factors that influence his or her survival become more and more pronounced. The Increasing significance, and its corresponding widening relative risk, for place of residence and Mothers status as a child grows from Neonates to Childhood, highlights the effect of social inequalities on child survival. This suggests that some social interventions, particularly when targeted at the mother, could help improve Child survival.